MINAT MAHASISWA PENDIDIKAN TATA KECANTIKAN TERHADAP GAYA RIAS MATA AEGYO SAL UNTUK RIAS PENGANTIN - Nadhiefa Dhiyaa Rizqy Zulfia; Abigail Eldaa Eleale; Suhandi, Naila Basmah; Adinda, Fitria Rama; Maria Krisnawati; Pramesti Adika Ratri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Aegyo Sal’s eye makeup from Korea began to attract attention in the world of Indonesian bridal makeup. This study aims to find out the interest of Beauty Education students in Aegyo Sal’s makeup style as inspiration in bridal makeup. The method used was quantitative descriptive through the distribution of questionnaires to 30 students of the beauty education program. The results show that most respondents have A high interest in this trend because it is seen as youthful, fresh, and suitable to be combined with modern bridal makeup in Indonesia.